Factors Influencing In-Game Impulse Purchase Among Last War: Survival Game Players - Andy Kurniawan; Fathin, Muhammad Qaishar; Aswin Dewanto Hadisumarto (Fakultas Ekonomi dan Bisnis Islam, 2025)
This study aims to analyze the psychological factors that affect impulse buying behavior in the mobile strategy game Last War: Survival, specifically the influence of competitive attitudes and the need for popularity on impulse purchase intentions, as well as the role of social competence moderation. The game implements an aggressive freemium business model and manages to create psychological and social pressures that drive status-based impulsive buying behavior. The research uses a conclusive-descriptive design with a cross-sectional approach. Primary data was collected through an online survey of 175 Last War: Survival players using purposive sampling techniques. All variables were measured with 35 indicators using a seven-point Likert scale. Data analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that competitive attitudes have a positive and significant effect on the need for popularity and impulse purchases in games. The need for popularity also has a significant effect on impulse purchases and has been shown to mediate a full relationship between competitive attitudes and purchasing behavior. Meanwhile, social competence has not been shown to moderate the relationship between variables. These findings confirm that in a highly competitive gaming environment, a player's competitive drive is converted into a need for social status which further triggers impulsive buying behavior, regardless of the player's level of social competence in the real world.